Gespräche mit Oppositionellen : Jürgen Fuchs, Lilo Fuchs, Utz Rachowski, František Černý, Marie Charousková, Bernd Eisenfeld, Rainer Eppelmann, Heinz Brandt, Stefan Brandt, Wolfgang Ullmann, Wolfgang Templin, Bärbel Bohley, Jens Reich, Sebastian Pflugbeil, Hans-Joachim Lazai, Jürgen Wiechert - Liebermann, Doris 1953- (Metropol, 2016)
Gespräche mit den Oppositionellen Jürgen Fuchs, Lily Fuchs, Uta Rachowski, Frantisek CernAP0, Marie Charousková, Bernd Eisenfeld, Rainer Eppelmann, Heinz Brandt, Stefan Brandt, Wolfgang Ullmann, Wolfgang Templin, Bärbel Bohlen, Jens Reich, Sebastian Pflugbeil, Hans-Joachim Lakai und Jürgen Wiechert